Effects of different frequencies of fire on an epigeal spider community in southern Caldenal, Argentina - Pompozzi, Gabriel Alejandro (2011)
Fire contributes to the selection and distribution of plant and animal species, and for a long time, its effects were considered to be negative. But recently, its role has been reinterpreted from a conservation standpoint. Fire, together with other environmental factors such as temperature and rainfall, affects the diversity and abundance of arthropods. Spiders comprise a group of potential ecological indicators, because they are diverse, abundant, and easy to sample, and they interact with their environment, potentially reflecting any ecological changes. Our goal was to assess the effects of controlled fires of different frequencies on the abundance, diversity, and composition of a community of epigeal spiders in southern Caldenal, La Pampa, Argentina. We obtained samples in May, Nov., and Dec. 2006 and Apr. 2007 in an area of approximately 12 ha. We conducted controlled burns every 3-4 and 6-7 yr since 1991, and used pitfall traps to collect specimens. Adults (554 spiders) were collected, and 56 species/morphospecies were recorded. Leprolochus birabeni Mello-Leitao 1942 (Zodariidae) was clearly the dominant species (19.9% of the total). We found significant differences in the abundances and species richness values between sampling months. However, we found no significant differences in the Shannon-Wiener (H´) diversity index between burned and unburned areas. The species compositions were similar in burned and unburned areas.